PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA INTERAKTIF WORDWALL TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS III SD - estri amaliya; Kiki Fatkhiyani; Piyantina Rukmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low interest and achievement of third-grade students in mathematics at SD Negeri 1 Grogol in the 2024/2025 academic year. To address this issue, the Make A Match model supported by Wordwall interactive media was applied to enhance students’ engagement and enjoyment in learning. Using a true experimental design with a pretest–posttest control group, Class III A (30 students) served as the experimental group and Class III B (30 students) as the control group, selected through random sampling. Instruments included a learning interest questionnaire and a learning achievement test, analyzed with the Mann- Whitney test. Findings indicated significant differences in both interest and achievement between groups, with Sig. values of 0.000 (α = 0.05). N-Gain results showed the experimental group achieved moderate improvement (0.31 for interest; 0.47 for achievement), while the control group remained low (0.21 for interest; 0.14 for achievement). These results confirm that the Make A Match model assisted by Wordwall has a significant positive effect on students’ learning interest and outcomes.